2016
DOI: 10.1177/0269215516651978
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Pilates exercise program in patients with chronic non-specific low back pain: a randomized controlled trial

Abstract: An 8-week Pilates exercise program is effective in improving disability, pain, flexibility and balance in patients with chronic non-specific low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 34 publications
6
63
0
6
Order By: Relevance
“…These results are similar to those found in other studies focused on the need for physical exercise in the promotion of better muscular health conditions 26,27 . Flexibility of boys and girls increased after the program.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to those found in other studies focused on the need for physical exercise in the promotion of better muscular health conditions 26,27 . Flexibility of boys and girls increased after the program.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies indicated that girls present more adequate levels of flexibility than boys 26,27,28 and also are more likely to engage in exercise to improve flexibility, therefore, we suggest future interventions take this into consideration as well as other strategies to reach a positive effect on the flexibility for boys.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Os estudos de forma geral mostraram efeitos positivos para o MP em pacientes com dor lombar crônica não especifica. Os principais benefícios do método apontados pelos estudos foram principalmente sobre o alivio da dor (CRUZ-DÍAZ et al, 2018;CRUZ-DÍAZ et al, 2015;MACHADO et al, 2017;MIYAMOTO et al, 2018;NATOUR et al, 2015;VALENZA et al, 2017), a maior na capacidade funcional (CRUZ-DÍAZ et al, 2018;CRUZ-DÍAZ et al, 2015;KOFOTOLIS et al, 2016;MACHADO et al, 2017;MIYAMOTO et al, 2018;NATOUR et al, 2015;VALENZA et al, 2017) principalmente em pessoas idosas, aumento da flexibilidade e mobilidade (CRUZ-DÍAZ et al, 2015;MACHADO et al, 2017;VALENZA et al, 2017), melhora no equilíbrio corporal (CRUZ-DÍAZ et al, 2015;LOPES et al, 2017;VALENZA et al, 2017), aumento da qualidade de vida (KOFOTOLIS et al, 2016;NATOUR et al, 2015), maior resistência muscular (MACHADO et al, 2017), e redução da cinesiofobia (CRUZ-DÍAZ et al, 2018) (tabela1). Sobre os estudos selecionados para a pesquisa, a maioria realizou ensaios clínicos randomizados (CRUZ-DÍAZ et al, 2018;KOFOTOLIS et al, 2016;MIYAMOTO et al, 2018;MOSTAGI et al, 2015;NATOUR et al, 2015;VALENZA et al, 2017), dois ensaio controlado aleatório único e cego (CRUZ-DÍAZ et al, 2015;LOPES et al, 2017) apenas um estudo de coorte prospectivo observacional (MACHADO et al, 2017).…”
Section: Resultsunclassified
“…Kofotolis, Kellis, Vlachopoulos, Gouitas, Theodorakis 32 reported that Pilates was more effective than trunk strengthening in increasing the quality of life and decreasing the functional disabilities after an 8-week protocol and the effects were retained for a three-month follow-up 32 . Studies that evaluated the effectiveness of a Pilates protocol compared to general exercises or self-management for eight weeks concluded that the method was more effective in reducing pain, disability, flexibility and balance in individuals with chronic LBP 21,22 . These authors also emphasized the importance of subgrouping these patients in order to create effective programs aimed at the specific mechanisms of pain, acting even more in the reduction of disability 22 .…”
Section: Discussionmentioning
confidence: 99%